KONDISI SOSIAL EKONOMI KELUARGA NELAYAN PUKAT CINCIN KECAMATAN SASAK RANAH PASISIE KABUPATEN PASAMAN BARAT - SARI, GUSFANIA; Suarto, Edi; Yuherman, Yuherman (STKIP PGRI Sumbar, 2013)
This studyaims to describe, obtaininformationanddiscuss(1) purse seinefishingfamily income, (2) the livelihoods ofpurse seinefishingfamilyside, (3) the level ofpurse seinefishingfamily educationand(4) the healthcondition of familypurse seinefishing.Type ofresearchis classifiedindescriptiveresearch. Populationofthis study are allpurse seinefishermenfamiliesresiding in DistrictSasakdomainsPasisiePasaman West, wherethere are217heads ofpurse seinefishing families. Researchsamplingwithproportionalrandom samplingtechniquewith25% of respondents54respondents.Data collectedbyinstruments, interviews, recordingandobservation. The data obtained wereanalyzedwithdescriptivestatisticspercentageformula.The resultsinclude: (1) Revenuepurse seinefishing familiesin the District ofSasakdomainsPasisie45respondents(83.33%) <Rp300.000/week, 43respondents(79.63%) are lessadequate forthe needs ofdaily live, 45respondents(83.33%) forchildrens education, 32respondents(59.26%) always for futurefamily, (2) the livelihoods offishing family sidelineis37respondents(68.52%) did nothavea second job, (3) family educationlevelof fishermen30respondents(55.56%) did notcomplete elementary school, 48respondents(88.89%) did nothave anformal education, 40respondents(74.07%) childrenof fishing familiesthrough education and 14respondents(25, 93%) of the children of fishermenwhodrop out of school, (4) the health condition ofthe familypurse seinefishing30respondents(55.56%) had suffered afluandfeverlastyear, 18respondents(33.33%) midwives/paramedicstreateda familyplacefishermen, 44respondents(81.48%) by using their own expensefor treatment.